The Impact of Customer Behavior on The Type of Household Expenditure.: Case Study (City of Vlora) - Kushta, Elmira; Ramosaco, Miftar; Memaj, Fatmir (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
This study focuses on the family, enabling data collection and processing to come to the conclusion that it spends on average a month in a family in the city of Vlora. The data was collected in written and electronic form with a form that was drafted following the study of many models performed in economically developed countries. Contribution was given by more than 100 families involved in the survey. This paper aims to look at the essence of decision-making by applying the mathematical methods that approximate the average cost per capita for the city of Vlora and are equal to 1 328 lek, the understanding of the basic concepts of these managerial and conceptual disciplines and to increase the level of application of these methods and principles among stakeholders in decision-making in all levels of politics, economy, society, etc.